Evaluation of effi cacy & safety of oral fi xed dose combination of probiotics in bacterial vaginosis - Arif Ahmed Faruqui (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2019)
Aim: To evaluate the effi cacy and safety of vaginal specifi c lactobacilli strain in management of bacterial vaginosis. Method: A non-randomized, open labeled, non-comparative, multi-centric, study was conducted in total of 58 female patients suffering from bacterial vaginosis. Each patient was administered a combination of four strains of Lactobacilli. Vaginal pH, discharge, odor, itching and painful urination were performed at baseline, week 2 and week 4 as assessment parameters. Result: At the end of study data was extractable in only 56 females (mean age was 34.57 ± 11 years). Associated BV symptoms like vaginal discharge, odor and painful urination reduced signifi cantly at week 4 as compared to baseline. The most frequently encountered symptom was vaginal discharge, vaginal pH, odor and itching. With a shift in pH<4.5, at the end of week 4 all females showed improvement in the vaginal microbiota. Tolerability of fi xed dose combination was found to be good and none of the subjects discontinued the treatment.